Energetic particles stimulating macro-scale zonal flow generation in ion-temperature-gradient turbulence - Yihan Wang; Zhibin Guo; Zhihong Lin (Nuclear Fusion, 2025)
We report a formation mechanism of macro-scale zonal flow (ZF) in ion-temperature-gradient (ITG) turbulence. Through gyro-kinetic simulations, it is found that the guiding centers of theenergetic particles (EPs) open a new dynamical coupling regime (∼a few EP gyro-radius) between the ITG turbulence and the ZF, so that the ITG turbulence produces a substantial global Reynolds force, which drives the macro-scale ZF. In addition, with the increase in the EP concentration, the ZF driven by a unit of turbulence intensity—the ZF capability—is enhanced correspondingly. A kinetic analysis reveals that the EPs stimulat macro-scale ZF generation through their strong in-phase effect with the ITG velocity fluctuations, which is rooted in the large diamagnetic drift frequency of the EP guiding center. We also carry out numerical experiments and show that in the presence of macro-scale ZF, the intensity of the nonlinearly saturated Alfvén eigenmodes would decrease. Thus, we potentially suggest a direct self-organization process for improving the EP confinement in burning plasma.